BE_VERWALTUNGSGERICHT 100 2017 332 vom 6. November 2017 - BE Verwaltungsgericht (2017)
Schülertransport (Entscheid der Erziehungsdirektion des Kantons Bern vom 6. November 2017; 4800.600.100.08/16 [750885]) | Bildung/Ausbildung